EFFECTIVE METHODS FOR DEVELOPING PROFESSIONAL SKILLS IN FUTURE DRAFTING (TECHNICAL DRAWING) TEACHERS - Taganov Ravshanbek Otaboyevich (Journals Park Publishing, 2025)
This article describes some pedagogical aspects of developing the professional competence of future teachers and their effective impact on the education system.
Keywords: Competence, teacher, multimedia, component, method, qualification, skill.